PERENCANAAN STRUKTUR HOTEL GET’S SEMARANG - Ricky Imanda; Ray Irwan Maulana; Nuroji Nuroji; Himawan Indarto (Jurnal Karya Teknik Sipil, 2014)
GET’S Hotel Building Semarang has an irregular shape. This building has a letter “L” shape. Separation of building (dilatation) is planned to transform an irregular building becomes a regular building. By construction of the regular building, it is expected the stiffnes and mass distribution tens to be coincide in position or at least be closer. In the condition, when the building shaking because of earthquake, it will cause a small torsion. Structure design of GET’S Hotel Semarang in this final project is designed by Special Moment Frame Bearer System (SRPMK) in Semarang’s seismic zone. By chosing Special Moment Frame Bearer System (SRPMK), it is expected the structure has a high ductility. Ductile structure is a kind of structure types which is able to has a large post elastic deviation repeatedly and frequently because of earthquake that caused the first yield and it is able to maintain the strength of the structure so that the structure remains standing in spite of  the edge of collapse. This structure is designed by using a capacity design of Strong Column Weak Beam. In this condition, the column structure is made stronger than beam structure, so that the part of the beam becomes the first plastic joints. The building will not be collapse totally when the strong earthquake occurs. The joints of the beam-column are designed to prevent the first collapse. The structure analysis of this building is based on SNI 03-1726-2012 and supported by SAP2000 v12 software which the results of the analysis are used to determine the fundamental period of the structure and the forces on the structure. Structural fundamental period on SRPMK has to be limited so that the structure is not very flexible.